Molecular Mechanisms and Therapeutic Prospects of Immunotherapy and Targeted Therapy in Primary Central Nervous System Lymphoma - Lin Zhong MM; Anqing Lu MB; Xiyue Lu MM; Xiaoyin Liu MD; Lujia Cao MM; Shihong Zhu MM; SiJun Diao MM; Xu Cheng MM; Hongwei Wu MB; Jing Chen MD (Technology in Cancer Research & Treatment)
Primary central nervous system lymphoma (PCNSL) is a very rare extranodal non-Hodgkin's lymphoma confined to the brain, eyes, spinal cord, and cerebrospinal fluid (CSF). This disease is highly aggressive. For decades, high-dose methotrexate-based induction regimens have been the standard treatment for PCNSL and have significantly improved patient overall survival (OS). However, some patients still experience disease recurrence or develop drug resistance. With a deeper understanding of the pathophysiology of PCNSL, various therapies, including CD20 monoclonal antibodies, Bruton's tyrosine kinase (BTK) inhibitors, immunomodulatory drugs, immune checkpoint inhibitors, phosphoinositide 3-kinase (PI3 K)/mammalian target of rapamycin(mTOR) inhibitors, and chimeric antigen receptor (CAR) -T cells are increasingly being applied and have demonstrated considerable efficacy. These therapies have paved the way for novel treatment strategies in PCNSL, representing a highly promising field. Investigating the mechanisms, specific targets, and signaling pathways, as well as interactions with the tumor microenvironment (TME), can provide a solid foundation for further exploration and potentially enhance the optimization of treatment approaches for PCNSL. This review seeks to explore the characteristics of the TME in PCNSL, elucidate the molecular mechanisms of various immunotherapies and targeted therapies, examine their interactions with the TME, and summarize the advancements in the research of PCNSL immunotherapy and targeted therapy.